Extreme Programming for Developing List Complain Feature Design on Griya Bayar System - Maharani, A.A.Sg. Mas Karunia (International Journal of Engineering and Emerging Technology, 2022)
Technological developments greatly affect various things, such as companies. Many companies’s process depend on technology and the most widely used are information systems. The information system that is widely accessed is the website. One of the companies is PT. Penkalis Sridanta usa a website on transaction process in PPOB Griya Bayar. However, there is a complex flow in complain list which is checking success or pending transaction process. They still use manual step and it’s make it need a lot of time during the process. Therefore, this journal discusses the development of the Complain List feature design using the Extreme Programming software development method. This method is suitable because of its flexibility and fast processing. The design of the Complain List feature consists of several stages such as planning, design, coding and testing. In the planning stage, we discuss user stories and scheduling. In the design phase there are CRC, Usecase, ERD and UI Design. At the coding and testing stages, other research can be carried out and it is hoped that it can be developed into a real system that can be used in real time.